REPUTASI AUDITOR DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA - DEWI KURNIA INDRASTUTI; VENIA MARIA DJOJO (Media Bisnis, 2020)
The purpose of this study is to analyze the impact of public accountant firm size, auditor specialization, company size, operating cash flow, leverage, return on assets, market to book value ratio, independent commissioners and firm age on earnings management. Purposive sampling method is used to obtain samples from manufacturing companies that listed in Indonesian Stock Exchange during 2015-2018. There are 71 companies meet the criteria and the hypothesis was tested using multiple linear regression analysis. The results indicate that company size, operating cash flow, leverage and return on assets have a significant effect on earnings management. Other independent variables such as public accountant firm size, auditor specialization, market to book value ratio, independent commissioners and firm age have no influence on earnings management.